URBAN LANDSCAPE AND DIGITAL PRESERVATION OF HERITAGE SITES: A CASE STUDY OF THE ANCIENT CITY OF SHANDAN IN GANSU, CHINA - ZHANG, WEIDI; KOLISNYK, O. (Art and Design, 2024)
Purpose of the study is to explore the application of digital technology in the preservation and restoration of ancient urban landscapes and heritage sites, with a specific focus on the Ancient City of Shandan in Gansu, China. Methodology. A review of relevant literature on digital preservation, the historical context of the ancient city of Shandan and the implementation of digital technologies such as 3D scanning, modelling and virtual reality. The methodology covers the detailed process of scanning and modelling key sites within Shandan, as well as assessing the outcomes of these digital preservation efforts through public VR experiences and educational applications. Results. The historical significance of the ancient city of Shandan and its strategic importance along the ancient Silk Road is highlighted. The use of digital technology has enabled the accurate preservation and reconstruction of key architectural elements and the cityscape. High-resolution aerial photography and photogrammetry were used to create detailed 3D models of the site, facilitating virtual tours, educational programs, and potential digital restoration of damaged structures. Pilot public VR experiences demonstrated the effectiveness of these models in enhancing public understanding and appreciation of Shandan’s cultural heritage. Scientific novelty lies in bringing the innovative application of digital technology to the conservation and restoration of the ancient city of Shandan. High-resolution data acquisition methods such as drone aerial photography and laser scanning were combined with advanced 3D modelling techniques to generate accurate and detailed digital images of the site. A comprehensive digital conservation approach is provided by accurately capturing the historical and architectural features of the ancient city of Shandan, including texture mapping to restore original materials and colours. Practical significance of this study lies in its demonstration of how digital technologies, such as 3D scanning, modeling, and virtual reality, can be effectively used to preserve and restore ancient urban landscapes. It provides a model for protecting cultural heritage and offers innovative methods to enhance public education and engagement with historical sites.